Subclinical LV Dysfunction Detection Using Speckle Tracking Echocardiography in Hypertensive Patients with Preserved LV Ejection Fraction - Amal Mohamed Ayoub; Viola William Keddeas; Yasmin Abdelrazek Ali; Reham Atef El Okl (Clinical Medicine Insights: Cardiology, 2016)
Background Early detection of subclinical left ventricular (LV) systolic dysfunction in hypertensive patients is important for the prevention of progression of hypertensive heart disease. Methods We studied 60 hypertensive patients (age ranged from 21 to 49 years, the duration of hypertension ranged from 1 to 18 years) and 30 healthy controls, all had preserved left ventricular ejection fraction (LVEF), detected by two-dimensional speckle tracking echocardiography (2D-STE). Results There was no significant difference between the two groups regarding ejection fraction (EF) by Simpson's method. Systolic velocity was significantly higher in the control group, and global longitudinal strain was significantly higher in the control group compared with the hypertensive group. In the hypertensive group, 23 of 60 patients had less negative global longitudinal strain than −19.1, defined as reduced systolic function, which is detected by 2D-STE (subclinical systolic dysfunction), when compared with 3 of 30 control subjects. Conclusion 2D-STE detected substantial impairment of LV systolic function in hypertensive patients with preserved LVEF, which identifies higher risk subgroups for earlier medical intervention.